Principles of Islamic International Criminal Law A Comparative Search - Malekian, Farhad (Brill's Arab and Islamic Laws Series, 2011)
The goal of this book is to minimize the misunderstandings and conflicts between International law and Islamic law. The objective is to bring peace into justice and justice into peace for the prevention of violations of human rights law, humanitarian law, international criminal law, and impunity. Readership: This book offers a peaceful resolution into international justice for researchers, students, practicing lawyers, military personnel, governmental officials, diplomats, judges, and prosecutors. It constitutes a prized addition to university and public library.